Entrepreneurial Education For Finger Disabilities Deaf Talk Training Through Processing Bread - Novfitri Landong Namora Sihombing Novfitri Sihombing; Siti Rozinah; Andri Meiriki (Ilomata International Journal of Social Science, 2020)
Competition increasingly harsh world of work and a lot of people who have not equalized the ability of the deaf to make them more challenging to grow and live independently. Still, there who think that people with smallpox are the ones who made the other person. Though there are still people with disabilities who have the talent and it can lift more appreciated in rank than the healthy surrounding environment. Could take the lesson that not all people with disabilities harm others. Normal Supposedly embarrassed and could make the experience from these people if see the concept, entrepreneurship be entrepreneurial while their entrepreneurship taste of the French language "Enterprende" which means to perform or carry out, while understanding the entrepreneur is one who organizes, manages and bears the risk of the business. Now, this entrepreneur also often include the inventor and developer of business, which can recognize and exploit opportunities. Convert chances into something worth performed and marketed. To grow themselves disabilities deaf, our team community service to choose the Finger Talk communities, as a forum to educate entrepreneurship training and processing and bread baking for friends disabilities deaf, from the training expected to foster the entrepreneurial spirit for disabilities friends and have expertise in making bread so that it can generate several kinds of food with some flavor.